Patient registries for home oxygen research and evaluation - Lacasse, Yves (Int J Chron Obstruct Pulmon Dis, 2019)
Randomized clinical trials are the preferred study design to address key research questions about the benefits or harms of interventions. However, randomized trials of oxygen therapy are difficult to conduct and have limitations. The purpose of this article is to offer our view on the potential use of patient registries in the field of home oxygen in COPD as an alternative to randomized trials by referring to the Swedish experience with a national registry for respiratory failure. Patient registries use observational study methods to collect uniform data (clinical and other) to evaluate specified outcomes for a population defined by a particular disease, condition, or exposure. As opposed to administrative databases, patient registries serve one or more predetermined scientific, clinical, or policy purposes. By systematically and prospectively compiling relevant data, patient registries may describe the natural history of a disease, determine effectiveness and cost-effectiveness, assess safety or harm, and measure quality of care. Registry-based randomized trials (ie, randomized trials within a clinical registry) combine the advantages of a prospective randomized trial with the strengths of a large-scale all-comers clinical registry. Challenges and issues in the design and implementation of patient registries include the representativeness of participants, data collection, quality assurance, ownership, and governance. Notwithstanding their limitations, patient registries represent valuable tools in the conduct of research in the area of home oxygen therapy.